Influence of π overlaminates on the mechanical behavior of all-composite adhesively bonded π joints. (May 2014) - Zhang, Jianyu; Zhao, Libin; Qin, Tianliang; Fu, Yue; Fei, Binjun
An all-composite out-of-plane adhesively bonded π joint is an effective structural connector for integrated aircraft structures. Its application can not only enable both the weight and assembly cost benefits, but also enhance the load-carrying capability. In composite π joints, the π shaped overlaminate is a significant kernel and thus attracts more attention of designers. With progressive damage analyses, the influences of π overlaminates with different configurations, lay-ups and geometric dimensions on the mechanical behaviors of composite π joints are obtained. The failure mechanisms and final failure loads of composite π joints with different π overlaminates are compared to provide more knowledge for the optimal design of such joints. Final failure loads stemmed from the static tensile experiments and physical failure phenomena of three types of π joints are presented. The good agreements between the numerical and experimental results not only validate the effectiveness of the numerical models, but also give evidence of the predicted tendency of strength improvement for composite π joints.